2022
DOI: 10.15517/am.v33i2.47223
|View full text |Cite
|
Sign up to set email alerts
|

New bacteria genera associated with rice (Oryza sativa L.) in Cuba promote the crop growth

Abstract: Introduction. The rice cultivar INCA LP-7 is one of the eleven principal cultivars in Cuba due to their high yield potential, salinity tolerance, and pathogens resistance. However, there are not reports about the isolation, identification, and characterization of bacteria associated to this cultivar that promote its growth. Objective. To select promising bacteria from the rhizosphere of the INCA LP-7 rice cultivar to promote the crop growth. Materials and methods. The investigation was carried out in 2015 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The bacterial community associated with the rhizosphere of cultivars INCA LP-5 and INCA LP-7 has been previously studied [ 25 , 26 ]. However, this is the first study describing the presence of bacteria in the seeds of both cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacterial community associated with the rhizosphere of cultivars INCA LP-5 and INCA LP-7 has been previously studied [ 25 , 26 ]. However, this is the first study describing the presence of bacteria in the seeds of both cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggests the possibility of developing and applying universal microbial inoculants to benefit global rice production. A previous study showed that around 64% of culturable strains from the rhizosphere of the rice cultivar INCA LP-7 belonged to the genus Pantoea [ 26 ]. Our result showed the presence of Pantoea as the bacterial endophytes of rice seeds from the cultivar INCA LP-7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation